Relationship between Iron Tablet Adherence and Anemia among Pregnant Women at Banda Sakti Health Center, Lhokseumawe - Nur Cantika Syafira; Dona Wirniaty; Indra Zachreini (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2026)
Anemia in pregnancy is a condition characterized by hemoglobin (Hb) levels below the normal threshold of 11 g/dL. This condition continues to represent a significant public health concern worldwide. Data from the World Health Organization indicate that the global prevalence of anemia among pregnant women reaches 41.8%. One of the main interventions for iron deficiency anemia is iron (Fe/ferrous sulfate) supplementation. Nevertheless, adherence to Fe tablet consumption among pregnant women remains inadequate, which contributes to the continued high prevalence of anemia. This study aimed to determine the association between adherence to Fe tablet consumption and the incidence of anemia among pregnant women at Banda Sakti Primary Health Center, Lhokseumawe. The findings revealed that most pregnant women with low adherence experienced anemia (90.5%), while the majority of those with high adherence had normal hemoglobin levels (69.2%). Statistical analysis demonstrated a significant relationship between adherence to Fe tablet consumption and the occurrence of anemia among pregnant women at the Banda Sakti Primary Health Center, Lhokseumawe.